Kajian “Struktur Fungsional” Emilie Durkheim Ditinjau dari Educational Anthropology on Character and Behavior Society - Wandi, Joni Indra; Afnita, Nora; Hefni, Hefni (Ikhtisar: Jurnal Pengetahuan Islam, 2021)
Emile Durkheim saw the social order of society emphasizes the importance of consensus, harmony, and equilibrium. To emerge the consensus harmony and equality of community-oriented should do creating the homogeneity and cultural values aimed for maintaining the social community order. This paper reveals the thought of Durkheim about the theory of consensus harmony and equilibrium based on maintaining a balance between knowledge, moral practice reasoning with ethical values ?? in the society through character education. The thinking side revealed how the public responds to changes in a dynamic culture of uncertainty with built social and cultural functions based on functional structure theory. This study discovers the education role in creating a moral being in modern society and moral being in building harmonic. It balanced with social functions through the solution to prevent and resolve any social pathology as the impact of the negative perception from social media. This expected explanation from this library research providing a positive contribution to character education and behavior to the society reviewed from the anthropological education study. The implication of this study for educators is the importance of building character and behavior order in the community comprehensively, kept up-to instill moral values, virtues, honest, law-abiding, and tolerance in creating a Madani's social life.